Training practices of male and female para athletics throwers: from developmental to world-class levels - Exal Garcia-Carrillo; Bruno Silva; Nikolaos Zaras; Rodrigo Ramirez-Campillo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: A better understanding of Para Athletics throwers (PAT) training practices is in line with the development and optimization of their training programs, able to produce peak performances across varying competitive levels.